EFFICACY OF JYOTISHMATI OIL WITH PRANAYAMA ON I.Q. (INTELLIGENCE QUOTIENT) - Pramod Shukla, Shailendra; Chitrakar, Mrudul (International Journal of Ayurveda and Pharma Research, 2015)
Aim of the Study: To evaluate the efficacy of Jyotishmati Oil with Pranayam on I.Q. (Intelligence Quotient). Objectives of the Study: To evaluate efficacy of Jyotishmati oil on mental age. To evaluate efficacy of Jyotishmati oil with Pranayama on mental age. To understand and explain precisely the concept of Jyotishmati oil as a Medha, Buddhi and Smruti enhancer by using modern parameter I.Q. Materials and Methods: Jyotishmati oil was procured from authorised pharmacy. Drug Authentification and Fingerprint analysis of Jyotishmati oil by HPTLC method was done from Certified Laboratory. The selected children were grouped in three groups, 30 children in each group. Group A and Group B considered as experimental group. In-group C no intervention was done. Route of administration - oral, Dose - 0.25ml twice a day, Anupan- Milk, Kala- After morning breakfast and after dinner. Duration- 180 days. Type of Study: Open Randomised Controlled Clinical Study. Assessment Criteria: The scores were taken before the trial (0th day) & after the completion of treatment schedule (180th day). All the groups were subjected to BKT or I.Q. and M.A. scores. Statistical Analysis: Student Paired t - test & Repeated measures ANOVA were used for statistical analysis. Result: The results were statistically analyzed for better interpretation. In comparison of both experimental group A and B and control group C, improvement in I.Q. and Mental Age were significant than control group C. In all the groups, Group B showed maximum improvement in Mental Age (M.A.).